Sources of Self-Efficacy to Teach Music among Non-Music Major Teachers in Primary School - Zainal Abidin, Nur Hawa; Jamaludin, Juriani (Environment-Behaviour Proceedings Journal, 2022)
This paper explores a qualitative study through semi-structured interviews with twelve non-music major teachers in primary school in Klang District, Selangor. The study suggests that teachers use various sources of self-efficacy to teach music. Verbal experiences in the form of lesson feedback appeared to be a particularly salient source for non-music teachers in this study. Based on the analysis, the non-music major teachers were influenced most by verbal persuasions, followed by vicarious experiences, physiological state, and mastery experiences. It comes together in conclusion, with verbal persuasion tending to override the other sources. Keywords: sources of self-efficacy; non-music major teacher; primary school music education eISSN: 2398-4287 Â© 2022.. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open-access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under the responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians), and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/ebpj.v7iSI7.3808